Determination of Website-Based Educational Assistance Recipients Using the Profile Matching Method at State Elementary School 9 Benteng - Wawa Salsabilla; Neni Mulyani; Elly Rahayu (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The development of information technology has brought about a major transformation in the field of education, particularly in the management of academic data and school administration. The process of determining educational assistance recipients at State Elementary School 09 Benteng is still done manually, thus potentially causing subjectivity. The absence of a website-based decision support system results in a less efficient selection process, suboptimal assessment results, and unstructured recipient criteria management. In addition, through the main discussion in this study aims to be able to design a website-based decision support system using the Profile Matching method to determine educational assistance recipients at State Elementary School 09 Benteng. This system is expected to support a more objective, structured and targeted selection process based on predetermined criteria. And in addition, the Research Method section used in this study is a descriptive quantitative approach. This method was chosen because the main objective of the study is not only to analyze a phenomenon, but also to design, develop, implement and test a website-based decision support system with the profile matching method. Based on the overall description in this study, the author can conclude that the website-based Decision Support System (DSS) for determining educational assistance recipients at State Elementary School 09 Benteng was successfully developed using the Profile Matching method to produce a more objective, structured and transparent selection process. This system replaces the previous, subjective manual method with a systematic assessment process, starting from determining criteria, weighting, calculating gap scores, and finally ranking. The results of data processing on 20 students showed that Maulana Malikul Ashori Putra obtained the highest score of 4,598 (rank 1), followed by Raka Dwi Kapo with the same score of 4,598 (rank 2) and Alfatin Rahma with a score of 4,540 (rank 3).